Salt-Inducible Kinases as Novel Therapeutic Targets for Diabetes Mellitus - Walukow, Clara Gabriela; Alfari, Nurrahmi; Damay, Viky Adrian (Current Internal Medicine Research and Practice Surabaya Journal, 2026)
ABSTRACT Diabetes mellitus remains a significant global health challenge because of inadequate glycemic control, underscoring the need for novel therapeutic strategies. Salt-inducible kinases (SIKs), members of the AMP-activated protein kinase (AMPK) family, have emerged as key regulators of glucose homeostasis by inhibiting hepatic gluconeogenesis and promoting glucose uptake.  This study conducted a literature search across multiple databases limited to articles published within the last ten years. The aim of this study is to examine the molecular mechanisms through which SIK isoforms influence glucose metabolism, their contribution to diabetes pathogenesis, and their promise as therapeutic targets. A review of recent studies indicates that all SIK isoforms enhance insulin sensitivities, glucose uptake and suppress glucose production in the liver. However, the working mechanisms of each isoform overlap and might be influenced by some variables. Pharmacological modulation of SIKs activity represents a promising strategy, although challenges related to isoform selectivity and off-target effects persist, and the optimal approach (activation versus inhibition) remains under debate. In conclusion, SIK isoforms constitute multifaceted targets for the treatment of diabetes mellitus, insulin resistance, hyperglycemia, and β-cell dysfunction. Further research is required to develop selective modulators and to assess their long-term safety and therapeutic efficacy.